POLA PENGELOLAAN KEUANGAN (PPK) BLUD DALAM UPAYA FLEKSIBILITAS PENGGUNAAN KEUANGAN DI UPT PUSKESMAS SUKAMARA - Muhammad Joni Chandra; Purwadhi, Purwadhi; Didin Syarifuddin (Journal of Innovation Research and Knowledge, 2025)
The purpose of this study was to determine the level of implementation of the flexibility of PPK-BLUD in Sukamara Health Center and the obstacles faced in the implementation process. This study adopts the concept of New Public Management which is translated by the government through the establishment of a Regional Public Service Agency system that aims to improve the quality of services to the community through financial management flexibility. The research method used in this research is descriptive qualitative with a case study approach. Data collection techniques used are Observation, Interview and Documentation. The results show that the flexibility that has been applied is the flexibility of income, expenditure, cash management, accounts receivable, goods management, human resource management (hr), remuneration, cooperation, reporting and accountability. While the flexibility that has not been implemented is the flexibility of debt, investment, SiLPA, service tariff. This is due to limited human resources in managing finances, the lack of local government regulations regarding technical guidelines for implementing BLUDs and the lack of synergy between stakeholders in optimizing the implementation of BLUD flexibility